The Potentiality of Plant Species from the Lamiaceae Family for the Development of Herbal Medicine in the Control of Diseases Transmitted by Aedes aegypti - Santos, Lizandra Lima; Brandão, Lethicia Barreto; Costa, Anderson Luiz Pena da; Martins, Rosany Lopes; Rodrigues, Alex Bruno Lobato; Almeida, Sheylla Susan Moreira da Silva de (Pharmacognosy Reviews)
The use of medicinal plants is an ancient practice used by man to treat various ailments and is expanding throughout the world. The so-called neglected diseases, such as dengue, yellow fever, Zika, and chikungunya transmitted by the A. aegypti mosquito, have affected and killed thousands of people. In this sense, the inclusion of herbal medicines in the public health system would help improve the quality of primary care provided for the population and serve as an alternative for vector control. In this context, as an alternative for chemical control of natural origin, herbal medicines that have insecticidal, larvicidal, and repellent action appear. Therefore, the present work aims to carry out a survey of some recent works related to the Lamiaceae family with potential for the development of herbal medicines for the control of diseases transmitted by Aedes aegypti, with an emphasis on promising technological innova tions with a repellent, insecticide and larvicide action mechanism. The article was developed through surveys of scientific and ethnobotanical information, using information from works published in Portuguese, English, and Spanish. The results proved the potential for the development of herbal medicines with a larvicidal, insecticidal, and repellent action mechanism for species belonging to the Lamiaceae family, presenting significant toxicity against insects, but negligible toxicity for animals, being easy to obtain, manipulate and apply, also presenting economic viability and non-cumulative effect on man and animals. The researches listed contribute to the feasibility of new biological tests that help in determining the most appropriate concentrations of phytoconstituents from extracts or essential oils that may be suitable for the formulation of repellents and other products for vector control.
Keywords: Herbal medicines; Lamiaceae; Vector control; Bioinseticidal; Repellent; Essential oil